n-EXPONENTIAL CONVEXITY FOR LEVINSON TYPE INEQUALITIES AND RELATED STOLARSKY TYPE MEANS - Vukelić, Ana (Matematichki Bilten, 2013)
Starting from the result given in [8] where the author gave the generalized Hadamard inequality, we give the generalizations of Levinson’s inequality (see [9]) and related inequalities. Also, we investigate the exponential convexity of differences of the left-hand and right-hand side of these inequalities. Using these differences, we produce new exponentially convex functions. They are used in studying Stolarsky type means.